ChemInform Abstract: Synthesis, Structure, and Properties of NaP7, a Phosphorus‐rich Polyphosphide. Issue 36 (September 2015) - Grotz, Carolin; Koepf, Marianne; Baumgartner, Maximilian; Jantke, Laura‐Alice; Raudaschl‐Sieber, Gabriele; Faessler, Thomas F.; Nilges, Tom
Abstract NaP7 is prepared from stoichiometric quantities of red phosphorus and Na in the presence of purified CuI as mineralizer (evacuated graphitized silica tubes, 823 K, 7 d).